The lysosomal storage disorders mucolipidosis type II, type III alpha/beta, and type III gamma: Update on GNPTAB and GNPTG mutations. Issue 7 (13th April 2019) - Velho, Renata Voltolini; Harms, Frederike L.; Danyukova, Tatyana; Ludwig, Nataniel F.; Friez, Michael J.; Cathey, Sara S.; Filocamo, Mirella; Tappino, Barbara; Güneş, Nilay; Tüysüz, Beyhan; Tylee, Karen L.; Brammeier, Kathryn L.; et al.
Abstract: Mutations in the GNPTAB and GNPTG genes cause mucolipidosis (ML) type II, type III alpha/beta, and type III gamma, which are autosomal recessively inherited lysosomal storage disorders. GNPTAB and GNPTG encode the α/β‐precursor and the γ‐subunit of N ‐acetylglucosamine (GlcNAc)‐1‐phosphotransferase, respectively, the key enzyme for the generation of mannose 6‐phosphate targeting signals on lysosomal enzymes. Defective GlcNAc‐1‐phosphotransferase results in missorting of lysosomal enzymes and accumulation of non‐degradable macromolecules in lysosomes, strongly impairing cellular function. MLII‐affected patients have coarse facial features, cessation of statural growth and neuromotor development, severe skeletal abnormalities, organomegaly, and cardiorespiratory insufficiency leading to death in early childhood. MLIII alpha/beta and MLIII gamma are attenuated forms of the disease. Since the identification of the GNPTAB and GNPTG genes, 564 individuals affected by MLII or MLIII have been described in the literature. In this report, we provide an overview on 258 and 50 mutations in GNPTAB and GNPTG, respectively, including 58 novel GNPTAB and seven novel GNPTG variants. Comprehensive functional studies of GNPTAB missense mutations did not only gain insights into the composition and function of the GlcNAc‐1‐phosphotransferase, but also helped to define genotype‐phenotype correlations to predict the clinical outcome in patients. Abstract : The lysosomal storage disorders mucolipidosis (ML) type II and III, trafficking of lysosomal enzymes in health and disease, and geographical distribution of disease‐associated GNPTAB and GNPTG mutations.